Endorphin Massage and Deep Back Massage for Pain During the Active Phase I of Maternity Mothers - Desi Br Sembiring (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Excessive pain will cause anxiety which can trigger the production of the hormone progstatglandin which can cause stress and affect the body's ability to withstand pain. Purpose: to assess Endorphin Massage and Deep Back Massage on Pain Intensity during the Active Phase I in Maternity. Methods: This is a quasi-experimental study using the two groups post test only design method. Samples were all mothers giving birth with accidental sampling technique as many as 20 people in the experimental group and 20 people in the control group for 6 months. Data analysis consisted of univariate and bivariate with Independent t-test. Results: The results showed that the intensity of labor pain in the group given Endorphin Massage and Deep Back Massage for mothers in labor showed a mild pain scale with a mean value of 4.95. The intensity of labor pain in the group that was not given Endorphin Massage and Deep Back Massage in laboring women showed a scale of severe pain with a mean value of 7.45. Conclusion: Endorphin massage and back deep massage have an effect on labor pain in the first stage of the active phase of labor with a p-value less than 0.0001 Abstrak: Nyeri yang berlebihan akan menimbulkan rasa cemas yang dapat memicu produksi hormone progstatglandin yang dapat menyebabkan stress dan mempengaruhi kemampuan tubuh menahan rasa nyeri. Tujuan: untuk menilai Massage Endorphin Dan Deep Back Massage Terhadap Intensitas Nyeri Kala I Fase Aktif Pada Ibu Bersalin. Metode: Penelitian ini Quasi experiment dengan metode two groups post test only design. Sampel adalah semua ibu bersalin dengan tehnik accidental sampling sebanyak 20 orang kelompok eksperimen dan kontrol 20 orang selama 6 bulan. Analisis data terdiri dari univariat dan bivariat dengan Independent t-test. Hasil: Hasil penelitian menunjukkan bahwa Intensitas nyeri persalinan pada kelompok yang diberikan Massage Endorphin Dan Deep Back Massage pada ibu bersalin menunjukkan skala nyeri ringan dengan nilai mean 4,95. Intensitas nyeri persalinan pada kelompok yang tidak diberikan Massage Endorphin Dan Deep Back Massage pada ibu bersalin menunjukkan skala nyeri berat dengan nilai mean 7,45. Kesimpulan: Massage endorphin dan back deep massage berpengaruh terhadap nyeri persalinan kala I fase aktif ibu bersalin dengan nilai p-value kurang dari 0,0001